2017
DOI: 10.1016/j.neuropharm.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational attenuation of opioid self-administration as a consequence of adolescent morphine exposure

Abstract: The United States is in the midst of an opiate epidemic, with abuse of prescription and illegal opioids increasing steadily over the past decade. While it is clear that there is a genetic component to opioid addiction, there is a significant portion of heritability that cannot be explained by genetics alone. The current study was designed to test the hypothesis that maternal exposure to opioids prior to pregnancy alters abuse liability in subsequent generations. Female adolescent Sprague Dawley rats were admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 64 publications
4
39
0
Order By: Relevance
“…Finally, some effects of maternal opioid exposure were transgenerational, as they were found in the F2 generation. For example, F2 females of F0 dams exposed to morphine during adolescence showed reduced morphine self-administrationsimilar to effects observed in the F1 generation [137]. Expression levels of a number of synaptic plasticity genes were examined in the nucleus accumbens of F1 and F2 males and females.…”
Section: Mu-opioid Receptorsmentioning
confidence: 97%
See 2 more Smart Citations
“…Finally, some effects of maternal opioid exposure were transgenerational, as they were found in the F2 generation. For example, F2 females of F0 dams exposed to morphine during adolescence showed reduced morphine self-administrationsimilar to effects observed in the F1 generation [137]. Expression levels of a number of synaptic plasticity genes were examined in the nucleus accumbens of F1 and F2 males and females.…”
Section: Mu-opioid Receptorsmentioning
confidence: 97%
“…Although there are numerous studies, particularly from the Byrnes lab [136,137], that explored multigenerational effects of parental opioid exposure, sex differences in direct effects on dopamine systems were not specifically reported. As such, this represents a gap in knowledge open to investigation.…”
Section: Key Playersmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of multigenerational and transgenerational opioid exposure studies have involved maternal opioid exposure (Byrnes, 2005;Byrnes et al, 2011Byrnes et al, , 2013Johnson et al, 2011;Vassoler et al, , 2016Vassoler et al, , 2017Vassoler et al, , 2018. However, a few studies have investigated behavioral and neurobiological differences in the offspring of opioid-exposed sires (Table 3).…”
Section: Opioidsmentioning
confidence: 99%
“…A growing body of evidence indicates that ancestral exposure to all of the major classes of abused drugs influences the physiology and behavior of descendants (Finegersh, Rompala, Martin, & Homanics, 2015;Finegersh, Ferguson et al, 2015;Szutorisz et al, 2014;Vassoler, White, Schmidt, Sadri-Vakili, & Pierce, 2013;Vassoler, Wright, & Byrnes, 2016;Vassoler et al, 2017;White, Vassoler, Schmidt, Pierce, & Wimmer, 2015;Yohn, Bartolomei, & Blendy, 2015). Several reports have consistently shown that sire exposure to cocaine influences cocaine-associated behaviors in the next generation.…”
Section: Introductionmentioning
confidence: 99%